Post-release Juvenile Offender at the Special Development Institute for Children in the Perspective of Sociology of Law - Syarif, Rahmat; Sabtu, Rahman Sandy Ela; Dukomalamo, M. Jufri (Journal of Legal Contemplation, 2025)
The aim of this research is to provide an understanding of the psychological condition of a child after being released from a foster child based on a legal sociology perspective at the Special Child Development Institute (LPKA). The research uses socio-juridical methods, including descriptive research with a non-doctrinaire approach, which views law as an empirical social phenomenon. The types and sources of data in this research use primary data and secondary data with data collection techniques in the form of documentation and literature study which is then analyzed descriptively qualitatively. The results of this research show that a bad view of former foster children in the social environment will result in children experiencing mental disorders, depression, low self-esteem, anxiety about hurting themselves and even suicide. The efforts made by the community and government are to accept and accommodate children who have problems with the law, so that there is a common perception between parents and the government in fulfilling children's rights, and avoiding bad views that have an impact on the survival and future of children.